Modern issues of giftedness: nature, structure and development - Karpova, L. (Problems of Engineer-Pedagogical Education, 2019)
The article is devoted to one of the important problems, which is a theoretical and methodological analysis of modern psychological and pedagogical views on giftedness. Giftedness consists of an individual original potential set of natural inclinations, a favorable social environment and personal potential, which make it possible to achieve significant success in a certain area of activity. The issue of giftedness contains a number of aspects, namely psychological, pedagogical, methodological, organizational, philosophical, social, etc. An independent multidimensional problem is the consideration of the creative potential of the individual, because it becomes expedient, while implementing an integrated approach, to take into account all possible trends and phenomena. The article highlights that in modern psychological and pedagogical thought there is no universal, recognized and accepted by all researchers definition of the concept of «giftedness». Through the prism of psychological encyclopedic data, giftedness is defined as a more general description of the scope of abilities, also pointing to an integrated approach to the study of the concept (psycho-physiological, psychological and socio-psychological). Attention is paid to the historical experience of studying the nature of giftedness, its origins and foundations, while emphasizing and analyzing an important issue of how modern science perceives the phenomenon of giftedness, its content, structure and development.